Currency swaps - Gamble, Fred; Plowright, Christopher (London : Financial i Production, 1986)
This video consists of two videos. Explain on the introduction of currency swaps, the fixed rate of currency swaps, currency coupon swaps, players and currencies, accounting, exposure and regulation
Two videos in one container + one book of training guide
Sponsored by Prudential Global Funding
Copy available in DVD format
Executive producer, Alastair Shaw ; writer, Will Hutton, Alastair Shaw, Fred Gamble ; editor, Damon Heath
Narrator: Peter Hobday
Keywords: Swaps (Finance).; Currency question